Clinico-etiological pattern of lower gastrointestinal bleeding in children (5-18 years age group) at a tertiary care center in central India - Bhadauria, Neha; Dubey, Shiv Ram Krishna; Mittal, Purvi; Arya, A K; Singh, R P (Indian Journal of Child Health, 2016)
Background: Lower gastrointestinal bleeding (LGIB), defined as bleeding occurring distal to the ligament of Treitz, is a common presenting symptom in pediatric patients. Objective: To understand the clinico-etiological pattern of LGIB in children in the age group 5-18 years. Materials and Methods: This prospective study was carried out at a tertiary health-care center in central India between January 2011 and August 2012. We consecutively enrolled all patients in the age group 5-18 years who came to our center with gross LGIB or two consecutive positive occult blood tests with at least 1-week interval between tests. All patients underwent colonoscopy (small, flexible Olympus PCF-20 colonoscope) and the findings were recorded. The procedure was done only after proper informed consent from the parents. Results: Total 38 patients were included in the study with above-mentioned inclusion and exclusion criteria, during the study period. Male to female ratio in LGIB was 2.16:1. LGIB was most common in children aged 5-10 years (63.1%), followed by 10-14 years (26.3%). Hematochezia was the most common presenting symptom (78.9%) followed by melena (21.1%). The most common causes of LGIB were colitis and colorectal polyp (31.6% each) followed by anal fissures (21.1%). Anemia was present in 68.4% patients at the time of presentation. Recurrence of LGIB was noted in 18 (47.4%) patients. Conclusion: We conclude that LGIB is most common in 5-10 years of children (school age) with hematochezia as the most common presenting symptom. Causes of LGIB in children in developing countries are same as developed countries (polyps and colitis being most common, followed by anal fissure), but further studies are required to determine the significant correlation between findings.